Contemporary trends in party organization: Revisiting intra-party democracy. (January 2020) - Borz, Gabriela; Janda, Kenneth
Party organization has regained a new momentum in the party literature over the past decade. In this context, we review the most important advances in the literature and critically examine issues such as: the link between party organization literature and organizational theory literature, party organization and intra-party democracy, and between party organization on paper and in reality. We ascertain the need for more conceptual clarifications in the field and raise questions for debate. We further outline the contribution of this special issue to the theme of intra-party democracy in representative democracies.